Against the flow, Mediterranean and Shipwreck according to Lina Prosa: translating to perform new collective imaginaries - Chirinos Bravo, Karín (Oltreoceano - Rivista sulle migrazioni, 2024)
This essay focuses on the representation of African immigration to Italy in Italian theatre through an analysis of Lina Prosa’s The Shipwreck Trilogy. Through a dramatic structure that ambivalently displays water as a site of life, transit and change, and as a site of tragedy, the Sicilian playwright denounces the many perils and difficulties faced by asylum seekers and economic migrants in Italy. At the same time, however, her plays also challenge the recurring westernization of the Mediterranean in an effort to debase its colonial envisioning as Mare Nostrum (the ancient Roman idea of the Mediterranean as the “sea of possessions”) and restore its meaining of “Mediterraneus”, i.e., “in the middle of the lands”, which thereby allows us to consider it as a bridge that unites different territories instead of dividing them. It is precisely this post-colonial envisioning of the Mediterranean as a meeting point for peoples and cultures and a place of hybridization that is embraced by Shauba, the protagonist of the first play in the trilogy, who refuses to consider the sea as a limit/border and the related notions of marginality it upholds. Prosa’s trilogy can thus be considered as part of what Lienhard calls oral writing, a practice which comprises «texts that collect or rework certain thematic, enunciative and poetic elements attributable to the oral discourse of the marginalized» (15). Prosa, indeed, breaks the silence of these marginal beings through the represented word, whose power goes beyond life and death, and beyond geographical and political borders. Her wisely oriented theatre, which is aimed at making the invisible visible, aptly intertwines the politics of criticism with the politics of resistance as it tries to tear down the walls of segregation from the global context and perform the right to exist as its absolute prerogative. In the second part of this essay, we explain the reasons that led us to translate and stage these plays in Peru, a country that was not only marked by strong internal migration, mainly from the Andes to Lima, during the twentieth century, but is also the destination of recent waves of intercontinental immigration flows from Venezuela.